2011 IEEE International Symposium on Biomedical Imaging: From Nano to Macro 2011
DOI: 10.1109/isbi.2011.5872584
|View full text |Cite
|
Sign up to set email alerts
|

Variational enhancement and denoising of flow field images

Abstract: In this work we propose a variational reconstruction algorithm for enhancement and denoising of flow fields that is reminiscent of total-variation (TV) regularization used in image processing, but which also takes into account physical properties of flow such as curl and divergence. We point out the invariance properties of the scheme with respect to transformations of the coordinate system such as shifts, rotations, and changes of scale. To demonstrate the utility of the reconstruction method, we use it first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Consistent with the recent trend in biomedical image processing-which favors total-variation (TV) type and L1 regularization-it is observed in Tafti and Unser [3] that the use of L1 norms in (1) leads in practice to better performance then the quadratic (L2) alternative in preserving discontinuities. This approach is further demonstrated in Tafti et al [7], where it is used to enhance the pathline visualization of blood flow in the aorta.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the recent trend in biomedical image processing-which favors total-variation (TV) type and L1 regularization-it is observed in Tafti and Unser [3] that the use of L1 norms in (1) leads in practice to better performance then the quadratic (L2) alternative in preserving discontinuities. This approach is further demonstrated in Tafti et al [7], where it is used to enhance the pathline visualization of blood flow in the aorta.…”
Section: Introductionmentioning
confidence: 99%
“…Continuing our previous line of work on vector field denoising and reconstruction in medical applications [2][3][4], in this paper we present a variational formulation and an algorithmic framework for Helmholtz decomposition of vector fields in the presence of noise. The essence of the formulation is to decompose the noisy vector field into three components: f cf (curl-free), f df (divergence-free), and n (noise), by minimising a suitable joint energy functional E( f cf , f df , n) subject to the constraint that these three components sum up to measurement vector y:…”
Section: Introductionmentioning
confidence: 93%
“…In practice, we work with discretised fields as well as discretised curl and divergence operators, which, in the simplest case, are based on finite differences [3,4]. Across field discontinuities (fluid interfaces, boundaries, etc.…”
Section: Problem Formulationmentioning
confidence: 99%
“…For instance, Suter and Chen [4] and Arigovindan et al [5] have considered them in the context of quadratic (L2) regularization. Tafti and Unser [6] and Tafti et al [7] have showed that the discontinuities at the flow boundaries are better preserved by switching from an L2-norm to an L1-norm regularization.…”
Section: Introductionmentioning
confidence: 99%
“…They are not truly suited for dynamic-flow imaging applications. In the present paper, based on our previous approaches on flow-field reconstruction [6,7,8], we introduce a variational method for time-dependent volumetric flow-field data.…”
Section: Introductionmentioning
confidence: 99%